Biodegradable Seaweed-Based Composite Films Incorporated With Calcium Carbonate Generated By Bacillus Sphaericus - Chong, Eunice Wan Ni (2021)
Seaweed-based films have been trending in the recent years due to its nutritional benefits, abundance, compatibility and biodegradability. However, the hydrophilic nature of seaweed film has been limiting its water barrier, mechanical and thermal performances. Therefore, this study is purposed to develop biodegradable film using raw red seaweed (Kappaphycus alvarezii) as a matrix and incorporated with microbially induced calcium carbonate precipitates (M-CaCO3) to further enhance the film performances. In order to determine the enhancement of film properties, seaweed-based composite films incorporated with different filler loading [0.06, 0.08, 0.10, 0.15, 0.20 and 0.50 (wt. %)] of M-CaCO3 were characterized based on physical, mechanical, thermal, biodegradability, morphological and crystallinity using various characterization techniques such as FESEM, EDX, FT-IR XRD and TGA. The properties of the films were then compared with the films incorporated with the commercial calcium carbonate (C-CaCO3). The optimum loading was attained by 0.15 wt. % M-CaCO3 and 0.10 wt.% C-CaCO3 based on the results of physical, mechanical and thermal properties. It has proven that moisture absorption and water vapour permeability was significantly (p<0.05) reduced while the contact angle, tensile strength, tensile modulus, elongation at break and thermal stability were significantly enhanced upon increasing filler loading from 0.06 wt. % up to 0.15 wt. % M-CaCO3 and 0.10 wt.% C-CaCO3 loadings, respectively.